2017
DOI: 10.17795/ijpbs-7670
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Transition in Smoking Stages in Iranian Adolescents: A Probabilistic Discrete Event System Model

Abstract: Background: Cigarette smoking is one of the most important public health problems. Objectives: This study determined the personal and environmental predictors of transition across smoking stages using cross sectional data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this study, the highest OR was found for the relationship between having an intimate drug-abusing friend and belonging to classes 2 or 3. Previous studies have recognized the importance of this factor, which has a positive relationship with the onset of drug abuse, increased drug abuse, and other high-risk behaviors [ 32 , 38 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest OR was found for the relationship between having an intimate drug-abusing friend and belonging to classes 2 or 3. Previous studies have recognized the importance of this factor, which has a positive relationship with the onset of drug abuse, increased drug abuse, and other high-risk behaviors [ 32 , 38 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the traditional models are restricted to a single probability of transition and do not produce the statistical significance for the effect of the covariates. 7 , 8 , 11 , 16 Furthermore, GMMs are not limited to the restricting statistical assumptions for estimating the parameters, which may not be satisfied in many practical situations. 17 - 19 These features propose GMMs in studies aiming at assessing transition through smoking stages, taking an advantage over the conventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, they are restricted to the certain statistical assumptions in the modeling process. 8 , 9 , 16 On the other hand, the advantages of newly established model, are: (1) GMMs have less bias and error, (2) give more detailed information, and (3) produce findings that are more accurate. 17 - 19 GMMs also relaxed some of the restricting statistical assumptions of the traditional models, so GMMs are feasible in practice.…”
Section: Introductionmentioning
confidence: 99%